2019
DOI: 10.3847/1538-3881/ab0ca1
|View full text |Cite
|
Sign up to set email alerts
|

On the Mass Accretion Rate and Infrared Excess in Herbig Ae/Be Stars

Abstract: The present study makes use of the unprecedented capability of the Gaia mission to obtain the stellar parameters such as distance, age, and mass of HAeBe stars. The accuracy of Gaia DR2 astrometry is demonstrated from the comparison of the Gaia DR2 distances of 131 HAeBe stars with the previously estimated values from the literature. This is one of the initial studies to estimate the age and mass of a confirmed sample of HAeBe stars using both the photometry and distance from the Gaia mission. Mass accretion r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 63 publications
3
49
0
Order By: Relevance
“…4 When drafting this manuscript, a paper by Arun et al (2019) was published reporting on the accretion rates using Gaia data of a somewhat smaller sample than here. Notable differences are that we use homogeneously determined stellar parameters for a large fraction of the sample and the fact that their sample is not selected for parallax quality and therefore includes faulty Gaia parallax measurements affecting the derived distances.…”
Section: Discussionmentioning
confidence: 99%
“…4 When drafting this manuscript, a paper by Arun et al (2019) was published reporting on the accretion rates using Gaia data of a somewhat smaller sample than here. Notable differences are that we use homogeneously determined stellar parameters for a large fraction of the sample and the fact that their sample is not selected for parallax quality and therefore includes faulty Gaia parallax measurements affecting the derived distances.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is observational evidence that points towards differences between the discs of low-and highmass PMS sources. This can be seen in the amount of infrared excess, which is much lower for high-mass sources (Ribas et al 2015;Vioque et al 2018;Arun et al 2019) or in morphology; for instance, spirals have only been found in early spectral type stars (Garufi et al 2018). Similarly, there is a clear observational bias in these results, as so far mostly long-lived, massive discs around low-mass stars have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty could in principle be reduced by averaging the results obtained from different emission lines [41]. The most recent L acc -L line empirical expressions for HAeBes including dozens of emission lines can be found in Fairlamb et al (2017) [64], and accretion rates inferred from this method (in particular, from the correlation with L Hα ) can also be found in the literature for hundreds of HAeBes [66,68].…”
mentioning
confidence: 99%